Anxiety and anger of homeless people coping with dental care. Issue 3 (15th February 2018) - Mago, Anjali; MacEntee, Michael I.; Brondani, Mario; Frankish, James
Abstract: Objectives: To reveal and describe from open‐ended interviews how homeless people in Vancouver interpret, appraise and cope with dental care. Methods: Audio‐recorded interviews with 25 homeless people (18 men and 7 women; age range: 25‐64 years), purposefully selected for a range of experiences, were transcribed and analysed inductively. The process of interpretive description drawing from the Behavioral Model for Vulnerable Populations and Lazarus's Theory of Emotions identified how participants appraised and coped with dental care. Results: Four dominant themes emerged: barriers to care; service use; opinions on dental health; and improving dental services. Participants were anxious about the cost of dentistry and fearful of dentists. They got emergency dental care with difficulty, usually in hospital emergency departments although mostly they preferred self‐treatment. They acknowledged the importance of dental health but felt stigmatized by their homelessness and visibly unhealthy mouths. They wanted accessible dental services with financial assistance from government, more widespread information about community dental clinics, and, notably among the Indigenous participants, less humiliating discrimination from dentists. Conclusions: Homeless people have difficulty coping with dental care. They believe that dentistry is frightening, humiliating and expensive, and governments are neither sympathetic to their disability nor willing to provide helpful information about community dental clinics or sufficient dental benefits for their needs.